Gambaran Efektivitas Tepung Biji Nangka (Artocarpus heterophyllus) sebagai Media Alternatif Pertumbuhan Jamur Aspergillus niger - Lia Mar’atiningsih; Sugiah Sugiah; Gina Nafsa Mutmaina; Mamay Mamay; Astari Nurisani; Muhammad Hadi Sulhan; Meti Rizki Utari; N.Ai Erlinawati; Noer Halisa Wardah (Jurnal Sains dan Kesehatan, 2024)
The culture medium functions to provide nutrition and as a place for microorganisms to grow optimally. The price of agar media is expensive and quite difficult to reach, making examination of microorganisms in the laboratory expensive. This can be overcome by using alternative media that are easy to obtain. One example of a natural ingredient that can be used as an alternative medium is jackfruit seeds which are then processed into flour. Jackfruit seeds can be used as an alternative ingredient because they contain nutrients, namely carbohydrates. The aim of this research was to see the effectiveness of jackfruit seed flour for the growth of the Aspergillus niger fungus. The type of research used is descriptive by describing the growth of the Aspergillus niger fungus on alternative agar media, namely jackfruit seed flour. . After data collection, the data is then processed using a tabulating stage which is presented in table form by showing the growth of the Aspergillus niger fungus macroscopically and microscopically using 10x and 40x magnification which is then grouped based on positive and negative categories.